The Effect Of The Application Of The News Presentation Towards Students’ Speaking Ability Of Grade Eleven At SMK Negeri 1 Seputih Agung - Risdiana Yusuf (Bandar Lampung University, 2015)
The objective of this research was to find and to observe the effect of the application of the news presentation towards students’ speaking ability of grade eleven at SMK Negeri 1 SeputihAgung. This was quantitative research. The data was collected by using observation (pre-test, treatment, post-test). The sample consisted of sixty students and they were divided into two classes. A class was as experimental group and another class was as control group. The research focused on speaking. It was a productive oral skill and it consisted of producing systematic verbal utterances to convey meaning in our daily life.In speaking, there were some components to understand such as grammar, pronunciation, vocabulary, fluency, and comprehension. The data collection was obtained from the tests. The pre-test was committed for the experimental and control group before the treatment. The post-Test was done for experimental and control group after the treatment. The data was analyzed by making use of t-Test of two group design. The results indicated that it was statistically significant p-value 1%=2,68 and 5%=2,01, t-value was 3,93 in order that p<t. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted so there was effect of the application of the news presentation towards students’ speaking ability. From the percentage, the research indicated that the application of the news presentation was successful in their speaking so that the researcher concluded that the news presentation was a good for teaching speaking in English